Previous lung volume reduction surgery does not negatively affect survival after lung transplantation. (8th September 2017) - Inci, Ilhan; Iskender, Ilker; Ehrsam, Jonas; Caviezel, Claudio; Hillinger, Sven; Opitz, Isabelle; Schneiter, Didier; Weder, Walter
Abstract: OBJECTIVES: Lung volume reduction surgery (LVRS) and lung transplantation (LTx) are the treatments of choice in selected patients with end-stage emphysema. Recently, the history of LVRS has been questioned due to reduced post-transplant survival. We aim to address this question by reviewing our experience, which is the largest single-centre series of LVRS followed by LTx. METHODS: We reviewed our prospectively recorded database in patients with emphysema undergoing LTx between 1993 and 2014. Preoperative workup and postoperative outcomes were compared according to previous LVRS status. The Kaplan–Meier test was used for survival analysis and compared with a log-rank test. RESULTS: One hundred and seventeen patients (66 men; mean age 56 ± 7 years) underwent LTx during the study period, 52 of whom had previous LVRS (LVRS + LTx). The mean time from LVRS to LTx was 45 ± 31 months. Patients were slightly older and had extensive smoking history in the LVRS + LTx group. Overall, in-hospital mortality was 10%, which did not differ significantly regardless of the history of LVRS ( P = 0.8). The median survival for the LTx-only and LVRS + LTx groups was 86 [95% confidence interval (CI) 56–116] and 107 (95% CI 77–137) months, respectively ( P = 0.6). CONCLUSIONS: Previous LVRS does not negatively affect short-term and long-term outcomes following LTx in patients with end-stage emphysema. The history of LVRS should not preclude the candidacy for LTx. Considering the limited number of donors available, the LVRS option should be kept in mind for the postponement of LTx in carefully selected patients.